Social isolation in a group living fish impairs cognition - Brandão, Manuela Lombardi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
To adjust to changes in the environment, animals can learn about the changes to help them modulate their behaviour as needed. Sometimes, however, changes in the social or the physical environment can generate fear states that trigger a physiological stress response which modifies an individual’s capacity to learn and can have a negative impact on the welfare of the animal. Social isolation, for example, besides being sressful for social animals, may provide less stimulation for these individuals. Here, we investigated whether social isolation impairs learning skills in a cichlid fish, Cichlasoma paranaense. Two treatments were compared, one with isolated individuals and another with dominant fish from a social group. The ability to associate a visual landmark with an accessible food reward was measured in a spatial task. Overall, fewer isolated fish were able to learn the task. The result was not because of a difference in general motivation to swim, feed, or explore the foraging options. The results indicate that social isolation for a normally social species of fish can impair learning

Para se ajustar a mudanças ambientais, os animais podem aprender sobre tais variações e modular seu comportamento de acordo com suas necessidades. Em alguns casos, no entanto, mudanças no ambiente social ou físico podem gerar estados de medo que levam a respostas de estresse fisiológico e que podem modificar a capacidade de um indivíduo em aprender, impactando negativamente o bem-estar desse animal. O isolamento social, por exemplo, além de estressante para animais sociais, pode proporcionar menor estimulação para esses indivíduos. Neste estudo, nós investigamos se o isolamento social prejudica habilidades de aprendizagem no ciclídeo Cichlasoma paranaense. Dois tratamentos foram comparados, um com indivíduos isolados e outro com peixes dominantes de um grupo social. A habilidade de associar uma pista visual com a comida acessível (recompensa) foi medida em uma tarefa espacial. De fato, menos peixes isolados foram capazes de aprender a tarefa. O resultado observado não se deveu a uma diferença na motivação geral para nadar, se alimentar ou explorar as opções de forrageamento. Os resultados indicam que o isolamento social para uma espécie de peixes normalmente social pode prejudicar a aprendizagem
Keywords: Ecologia animal; Peixe - Comportamento; Animais - Inteligencia; Isolamento social; Animal Proteção; Animal ecology